Monitoring annoyance and stress effects of wind turbines on nearby residents: A comparison of U.S. and European samples. (November 2019) - Hübner, Gundula; Pohl, Johannes; Hoen, Ben; Firestone, Jeremy; Rand, Joseph; Elliott, Debi; Haac, Ryan
Abstract: As wind turbines and the number of wind projects scale throughout the world, a growing number of individuals might be affected by these structures. For some people, wind turbine sounds and their effects on the landscape can be annoying and could even prompt stress reactions. This comparative study analyzed a combined sample of survey respondents from the U.S., Germany and Switzerland. It utilized a newly developed assessment scale (AS-Scale) to reliably characterize these stress-impacted individuals living within populations near turbines. Findings indicate low prevalence of annoyance, stress symptoms and coping strategies. Noise annoyance stress (NAS-Scale) was negatively correlated with the perceptions of a lack of fairness of the wind project's planning and development process, among other subjective variables. Objective indicators, such as the distance from the nearest turbine and sound pressure level modeled for each respondent, were not found to be correlated to noise annoyance. Similar result patterns were found across the European and U.S. samples. Highlights: Residents stressed by wind turbines represent a small proportion of the population. Lower prevalence of stress related annoyance compared to single annoyance assessment. Experienced planning process related to stress by wind turbine noise, distance not. Average attitude toward the local wind farm is positive. Similar result patterns found in the U.S. and European samples.